Field evaluation of the novel One Step Malaria Pf and Pf/Pv rapid diagnostic tests and the proportion of HRP-2 gene deletion identified on samples collected in the Pwani region, Tanzania - Mwangonela, Zena E. (2023)
Malaria rapid diagnostic tests (mRDTs) have played an important role in the early detection of clinical malaria in an endemic area. While several mRDTs are currently on the market, the availability of mRDTs with high sensitivity and specificity will merit the fight against malaria. We evaluated the field performance of a novel One Step Malaria (P.f/P.v) Tri-line and One Step Malaria (P.f) rapid test kits in Pwani, Tanzania.